PENGGUNAAN TANAH HAK PENGELOLAAN OLEH PIHAK KETIGA - Urip Santoso (Faculty of Law, Universitas Jenderal Soedirman, 2013)
Management Right holders authorized to use the land for the purpose of implementation of tasks or business, is also authorized to submit portions of land right and management to third parties or to cooperate with the third parties in the form of land use agreements which publishes Right to Build or Right to Use, and in the form of the release of land rights which publishes Right of PropertyKeywords: right of management, right to build, right to use, right of property